“Should I Stay or Should I Go?”: A Multiple-Criteria Group Decision-Making Approach to SME Internationalization - Rosário, M.; Ferreira, F.; Çipi, A.; Pérez-Bustamente, G.O. (2019 International Conference on Digital, Innovation, Entrepreneurship and Financing, 2019)
Due to domestic markets’ current economic conditions, companies increasingly feel that they need to become actively involved in international trade. However, small and medium-sized enterprises (SMEs) typically face financial and intellectual constraints during internationalization processes. This means that decision makers must consider a wide range of different variables before deciding to internationalize firms. This study sought to integrate cognitive mapping and the Decision EXpert (DEX) method in order to develop a multiple-criteria decision model suitable for the identification and assessment of variables influencing SMEs’ internationalization capability. The results confirm that the dual methodology adopted facilitates the development of a robust evaluation model that can improve decision-making processes in the context in question. More specifically, the proposed model identifies product features as the most important factor in SMEs’ capability for successful internationalization. In addition, internal factors are significantly more relevant than external factors. The model-building process is discussed, including its advantages and limitations.